FMNL1 and mDia1 promote efficient T cell migration through complex environments via distinct mechanisms - Sigler, Ashton L.; Thompson, Scott B.; Ellwood-Digel, Logan; Kandasamy, Adithan; Michaels, Mary J.; Thumkeo, Dean; Narumiya, Shuh; Del Alamo, Juan C.; Jacobelli, Jordan (Frontiers in Immunology, 2024)
Lymphocyte trafficking and migration through tissues is critical for adaptive immune function and, to perform their roles, T cells must be able to navigate through diverse tissue environments that present a range of mechanical challenges. T cells predominantly express two members of the formin family of actin effectors, Formin-like 1 (FMNL1) and mammalian diaphanous-related formin 1 (mDia1). While both FMNL1 and mDia1 have been studied individually, they have not been directly compared to determine functional differences in promoting T cell migration. Through in vivo analysis and the use of in vitro 2D and 3D model environments, we demonstrate that FMNL1 and mDia1 are both required for effective T cell migration, but they have different localization and roles in T cells, with specific environment-dependent functions. We found that mDia1 promotes general motility in 3D environments in conjunction with Myosin-II activity. We also show that, while mDia1 is almost entirely in the cytoplasmic compartment, a portion of FMNL1 physically associates with the nucleus. Furthermore, FMNL1 localizes to the rear of migrating T cells and contributes to efficient migration by promoting deformation of the rigid T cell nucleus in confined environments. Overall, our data indicates that while FMNL1 and mDia1 have similar mechanisms of actin polymerization, they have distinct roles in promoting T cell migration. This suggests that differential modulation of FMNL1 and mDia1 can be an attractive therapeutic route to fine-tune T cell migration behavior.